The Management Orphanage in Henri Fayol's Perspective: A Case Study of the Lembaga Kesejahteraan Sosial Anak (LKSA) Darul Hadlonah Ceper Klaten - Fardani, Diah Novita; Trihastuti, Meiwatizal; A. Hasyim, Umar Al Faruq; Reni Andriyani (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This article was to find out the substance framework of Henry Fayol's theory, to know the application of management Lembaga Kesejahteraan Sosial Anak (LKSA) Darul Hadlonah Ceper Klaten, and to find out the relevance of Henry Fayol's managerial practice theory applied to the Orphanage LKSA Darul Hadlonah Ceper Klaten. The researchers used qualitative research. Observation and interviews was used in collecting the data. The results indicated that the implementation management Orphanage of LKSA Darul Hadlonah Ceper Klaten in the functions of planning, command or giving orders, coordinating and controlling were going well. The planning system was adjusted to the timeframe that would be needed. Hence, the implementation of planning management was running well. Being able to jointly be responsible with everything related to the utilization of facilities, equipment and personnel needed.